Carbon Credit and Macaúba Palm Tree: Advancing ESG in Green Cattle Production - Glaucia Fernandes Vasconcelos; Victor Almeida (RAC: Revista de Administração Contemporânea)
This case aims to explore the intersection between the financial sustainability of cattle production, the sale of carbon credits, and the cultivation of macaúba palm trees. The case identifies challenges and opportunities for ESG (environmental, social, and governance) practices in the context of contemporary agribusiness. The account involves a Brazilian rural farmer and presents the planting process and integration of macaúba palm with beef cattle production, the concept of the carbon market, and the social externalities of the project. The case raises the following dilemma: How to balance the economic potential of macaúba palm trees and their byproducts with the mission of producing cattle in an ecologically responsible manner while positioning favorably in the carbon credit market? The pedagogical objectives focus on analyzing the economic, financial, and environmental feasibility of integrating green cattle production and macaúba palm cultivation, understanding the dynamics and implications of carbon credits in the national agribusiness context, and reflecting on the importance and challenges of implementing ESG practices in agribusiness, this way stimulating the decision-making capacity in complex and multidimensional scenarios. The case can be applied in undergraduate and graduate level courses in finance and related fields. The case is recommended to encourage students to reflect on the financial structures and challenges of implementing the sale of carbon credits for small rural landowners.